2020
DOI: 10.36108/pajols/0202/40(0110)
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Identification and Insecticide Resistance Status of Culex mosquitoes collected from blocked drainages in Lagos State, Nigeria

Abstract: Background: Culex mosquitoes are important vectors of several human pathogens causing infections such as lymphatic filariasis and several viruses. Poor and blocked drainage system can lead to impediment in water flow, leading to the artificial creation of larval habitats for Culex mosquitoes. Culex mosquitoes has the ability to breed in organically polluted water bodies and exhibit high resistance to insecticides. Therefore, this study assessed the species and insecticides susceptibility status of Culex breedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Generally, there was no mortality recorded in the control experiments in the present study. Thus there was no need for the use of Abbott's formula [20]. Also, the mosquito larval population used in this study is a naturally thriving as no mortality was recorded in the control experiments.…”
Section: Resultsmentioning
confidence: 97%
“…Generally, there was no mortality recorded in the control experiments in the present study. Thus there was no need for the use of Abbott's formula [20]. Also, the mosquito larval population used in this study is a naturally thriving as no mortality was recorded in the control experiments.…”
Section: Resultsmentioning
confidence: 97%
“…This has prompted a considerable change in the distribution of mosquito species with an associated persistence in disease prevalence (Beebe, 2018). Mosquitoes of the genus Culex are of notable public health concerns due to their vectoral capacity to transmit several human disease pathogens including West Nile virus, encephalitis virus, and elephantiasis (Agbor et al 2020;Aremu et al 2022). Importantly, the population dynamics and the diversity of species have been observed to impact the intensity of transmission of mosquito-borne diseases (Adeleke, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Genetic variations among vectors in different countries have been reported to be responsible for disease transmission (Gupta et al 2016). Several studies in Nigeria have reported mosquito identity using conventional morphological methods (Adeleke et al 2013;Afolabi et al 2019;Agbor et al 2020). This identi cation tool is inadequate to distinguish morphologically similar but genetically distinguishable of species in a complex.…”
Section: Introductionmentioning
confidence: 99%